Reflections of the Benedictine Rule in Bede's Homiliary - Walt, A. G. P. van der (The journal of ecclesiastical history, 1986)
The rule which Benedict Biscop had laid down for the monastery of St Peter and St Paul at Wearmouth and Jarrow is twice mentioned in some detail in the writings of the Venerable Bede. Unfortunately both passages are rather vague in that no clear indication is given of which particular rule Biscop introduced at Wearmouth–Jarrow. It is certain, however, that Biscop did not compose a totally new rule, but accepted for his own houses the monastic institutes which he had learned abroad.